Chemo‐Biocatalytic Oxidative Condensation of Natural Arylpropene with 2‐Aminobenzothiazole into Schiff‐Bases as Potent Anti‐Amyloid Agents: Studies Employing Transgenic C. elegans. Issue 12 (30th March 2018) - Saima; Kumar, Lalit; Lavekar, Aditya G.; Sharma, Tanuj; Shamsuzzama; Equbal, Danish; Siddiqi, Mohammad Imran; Sinha, Arun K.; Nazir, Aamir
Abstract: Combining natural scaffolds with potent heterocyclic pharmacophores to have extra ordinary potency of synthetic hybrid molecules has gained significant attention as these compounds possess diverse biological activities including ameliorative effects against Alzheimer disease (AD) associated endpoints. In this context, a chemo‐biocatalytic protocol has been described wherein 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone (DDQ) catalyzed oxidation of natural methoxylated phenylpropenes into corresponding cinnamaldehydes followed by Bovine serum albumin (BSA)‐catalyzed condensation reaction with heterocyclic amine in water provides a series of Schiff bases in moderate to good yield. Interestingly, some of the 2‐aminobenzothiazole based Schiff bases with dioxymethylene substituted cinnamaldehydes, an oxidized product of natural isosafrole, appear as an multifunctional agents which significantly decreased the disease associated endpoints in C. elegans model of Alzheimer's disease. These Schiff bases exerted their effect by reducing Aβ aggregation, decreasing lipid deposition and oxidative stress, thereby preventing cholinergic neuronal degeneration. All these properties highlight the therapeutic potential of these prototypes to be developed as new multifunctional drug candidates in the treatment of Alzheimer's disease. Moreover, molecular modeling studies have revealed the interaction of Schiff base with acetylcholine receptors. Abstract : Cinnamaldehyde‐aminobenzothiazole based Schiff bases have been synthesized by chemo‐biocatalytic process and explored as multifunctional agents against Alzheimer's disease. Which exerted their effect by reducing Aβ aggregation, decreasing lipid deposition, thereby preventing cholinergic neuronal degeneration possibly via pathways that modulate excitatory neurotransmission and via ameliorating aggregation of proteins.